Diagnosis of Follicular Lesions of Undetermined Significance in Fine-Needle Aspirations of Thyroid Nodules. (24th March 2013) - Ratour, J.; Polivka, M.; Dahan, H.; Hamzi, L.; Kania, R.; Dumuis, M. L.; Cohen, R.; Laloi-Michelin, M.; Cochand-Priollet, B.
Abstract : Aim . We aimed to analyze the diagnostic criteria proposed by the Bethesda System for Reporting Thyroid Cytopathology for follicular lesions of undetermined significance (FLUS), the risk of cancer and diagnostic improvement with use of immunocytochemistry. Methods . For each FLUS diagnosis, we analyzed the cytological criteria (9 Bethesda criteria), secondary fine-needle aspiration (FNA) results, surgical procedures, contribution of immunocytochemistry with the antibodies cytokeratin 19 (CK19) and monoclonal anti-human mesothelial cell (HBME1). Results . Among patients with 2, 210 thyroid FNAs, 244 lesions (337 nodules) were classified as FLUS (11% of all thyroid FNAs). The 3 criteria most often applied were cytological atypia suggesting papillary carcinoma (36%), microfollicular architecture but sparse cellularity (23.1%), cytological atypia (21.5%). With secondary FNA, 48.8% of nodules were reclassified as benign. For about half of all cases (41.4% for the first FNA, 57.6% for the second FNA), immunocytochemistry helped establishing a diagnosis favoring malignant or benign. No benign immunocytochemistry results were associated with a malignant lesion. In all, 22.5% of the 39 removed nodules were malignant. Conclusion . The FLUS category is supported by well-described criteria. The risk of malignancy in our series was 22.5%. Because we had no false-negative immunocytochemistry results, immunocytochemistry could be helpful in FLUS management.